(untitled) - Roger Leslie Timings (1927- (London, 1997)
The book provides an essential overview of all topics of production and manufacturing engineering. It is organized into two sections, it discusses both the technology of manufacturing and management of manufacture. The main manufacturing processes are detailed including: casting, flow-form, sintered particulate processing, plastic moulding, cutting, assembly, advanced manufacturing technology, measurement and testing techniques. The section on management of manufacture takes into account health and safety issues, cost control, the control of manufacture and lastly, but of increasing importance, quality issues in manufacture. Over 300 diagrams and 34 photographs support the book
Keywords: manufacturing processes,mechanical engineering